2020
DOI: 10.3382/ps/pez462
|View full text |Cite
|
Sign up to set email alerts
|

Maternal conjugated linoleic acid alters hepatic lipid metabolism via the AMPK signaling pathway in chick embryos

Abstract: The effects of maternal conjugated linoleic acid (CLA) on embryonic development and hepatic lipid metabolism were investigated in chick embryos. A total of 180 Arbor Acres female broiler breeders (36 wk old) were randomly divided into the following 3 dietary treatment groups: a basic diet (control), a basic diet containing 0.5% CLA (CLA1), and a basic diet containing 1.0% CLA (CLA2). The females were fed for 8 wk, and the eggs from each group were collected and hatched during the last 2 wk. The results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 60 publications
3
23
1
Order By: Relevance
“…After signal path enrichment analysis, we found that the DEMs were significantly enriched in the metabolic pathways of the linoleic acid (3/4 metabolites), taurine and hypotaurine (4/6 metabolites), AA (14/31 metabolites). These pathways are important for anti-inflammatory and immune responses during infection [ 34 , 35 ]. Studies have shown that pathway impact greater than 0.1 means that the pathway has enriched, and greater than 0.4 means significant enrichment [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…After signal path enrichment analysis, we found that the DEMs were significantly enriched in the metabolic pathways of the linoleic acid (3/4 metabolites), taurine and hypotaurine (4/6 metabolites), AA (14/31 metabolites). These pathways are important for anti-inflammatory and immune responses during infection [ 34 , 35 ]. Studies have shown that pathway impact greater than 0.1 means that the pathway has enriched, and greater than 0.4 means significant enrichment [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that oxylipin metabolites can regulate the AMPK signaling pathway [27][28][29][30]. e results showed that although the phosphorylation of AMPK was not significantly different in the model group compared with the control group, PZH-H intervention markedly promoted the phosphorylation of AMPK (Figure 7(a)).…”
Section: Effect Of Pzh On Ampk-acc-cpt1a Pathwaymentioning
confidence: 74%
“…Previous studies have proved that EPA could improve palmitate-induced endothelial dysfunction and lipotoxicity by activating AMPK pathway [ 28 , 48 ]. In addition, LA can reduce hepatic lipid metabolism [ 29 , 30 ], insulin resistance, and adiposity [ 49 , 50 ] via the AMPK pathway. PGE2 can negatively regulate the AMPK pathway [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of linoleic acid leads to a significant decline in the growth rate of animals, causing reproductive obstacle diseases and disorders of lipid metabolism in the body. Fu et al (2020) have shown that supplementation of maternal conjugated linoleic acid (CLA) could reduce lipid synthesis through the AMP-activated protein kinase (AMPK) signal pathway in chicken embryo liver. Therefore, we speculate that the decrease of laying rate and the increase of liver fat deposition in FLHS laying hens may be related to the decrease of serum unsaturated fatty acid content.…”
Section: Discussionmentioning
confidence: 99%